Prioritas Pemakaian Anggaran Pada Klinik Kesehatan Berbasis Metode Simple Additive Weighting - Karmila, Karmila; Kusumaningrum, Lely; Karmila; Setiawan, Aries; Prawitasari, Dian; Dian Andika , Arditya; Sjamsul Hidajat, Moch; Prasetya, Jaka; Hallang Lewa, Andi (Jurusan Teknologi Informasi Universitas Semarang, 2025)
Financial management that is less careful and less able to choose each expense will have an impact on the imbalance of income and clinic expenses, if it happens continuously will cause the clinic to gradually be unable to operate anymore. Each type of clinic expense certainly has a different level of importance, the level of importance is influenced by various variables such as the nominal expenditure, deadline date, user of the expenditure, level of importance, purpose of use. The problem that occurs is that the fulfillment of the needs of the clinic is often unable to prioritize expenses or without considering the level of importance of expenses. There needs to be an appropriate priority scale to regulate the level of expenditure that will impact the financial security of the clinic so that it can support the smooth operation of the clinic, with the aim that the clinic will be able to grow or develop for the smooth provision of health services to the community. One method that can be implemented to help prioritize the use of the clinic budget is simple additive weighing. From the results of the comparison between the ranking of the old model and the ranking using the simple additive weighing method, there are two different sequences, namely codes A7 and A14, resulting in a 90% accuracy rate.